2022
DOI: 10.1177/13540688221080537
|View full text |Cite
|
Sign up to set email alerts
|

Membership and participation in independent local parties: Patterns and explanations

Abstract: Despite the rising electoral success of independent local parties in many European countries, empirical evidence about their members is still rare. Therefore, the study aims to answer three questions to reach new insights: Who are these members? Which incentives motivate them to join, and how is intra-party participation structured? Based on a cross-sectional postal survey in Germany, the results show that members of independent local parties and national parties have mostly the same socioeconomic background a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 53 publications
0
2
0
Order By: Relevance
“…The variable national attachment is measured in the ESS with a ten-point scale ranging from not at all emotionally attached (0) to very emotionally attached (10). Additionally, following the findings on the relevance gender and age have on the likelihood of party membership (Achury et al, 2020;Angenendt, 2023), our model controls for gender and age.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The variable national attachment is measured in the ESS with a ten-point scale ranging from not at all emotionally attached (0) to very emotionally attached (10). Additionally, following the findings on the relevance gender and age have on the likelihood of party membership (Achury et al, 2020;Angenendt, 2023), our model controls for gender and age.…”
Section: Methodsmentioning
confidence: 99%
“…Research has demonstrated that party members compose a rather homogenous group of citizens that does not mirror the diversity in the population (Achury et al, 2020;Angenendt, 2023). Focusing on citizens of immigrant origin (CIO), characterized by their diversity in terms of ethnicity, religion, race, and language, studies have identified barriers immigrants face while incorporating themselves into political parties and becoming elected representatives (Dancygier et al, 2015;Zapata-Barrero, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…It is anything but a foregone conclusion that the Free Voters' formula for success in local politics can easily be transferred to federal politics. According to the thesis of second-order elections (Reif and Schmitt 1980), voters are more likely to cast "protest" votes in local elections than federal ones, with the result that the established parties have greater competition from the independent local lists who benefit from voters' distrust in the established parties (see Jankowski et al 2022a;Angenendt 2018Angenendt , 2023. Thus, the conditions of party competition in higher-level politics differ from those in local politics.…”
mentioning
confidence: 99%